Dampak Pembelajaran Daring terhadap Hasil Belajar Matematika pada Pembelajaran New Normal Siswa Kelas V SD - Ahmat Wakit (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2023)
The purpose of this research is to find out the impact of online learning on offline learning in the new normal era in mathematics courses and to find out the perceptions of parents and students about online learning. This type of research is descriptive qualitative. The research subjects were fifth-grade students at SDN 04 Krapyak Jepara. Data collection techniques used are interviews, observation, tests, and documentation. The stages of data analysis used in the research include data collection, data reduction, presentation, and conclusion. The results of the study show that online learning has both positive and negative impacts. The positive impacts are (1) parents have a lot of time accompanying children, (2) students are used to studying at home. The negative impacts of online learning on mathematics learning in the new normal era include; (1) students becoming less focused, (2) students having difficulty understanding math material because they do not understand the basics of multiplication and division, (3) students having difficulty remembering formulas, (4) some students have difficulty communicating with teachers, (5) tendency to play cellphones at home increase. It can be seen that the impact of online learning on mathematics learning in the new normal era is that students still do not understand the concept of multiplication and division so students have difficulty understanding mathematics material which causes low student learning outcomes. Keywords: online learning, mathematics learning outcomes, new normal era